The Digital City: Using the Example of "Mönchengladbach on eBay". - Heinemann, Gerrit; Wenzel, Stefan (Springer, 2018)
The digital revolution inevitably alters brick and mortar retailers. In particular, retail cities face enormous challenges. If they want to survive as a retail location, they have to improve their image and work on their appeal for digitally oriented customers. These cities need to digitalize their infrastructure. Local retailers must go online. Retail has to be reinvented to create new kinds of digital experiences. It needs to integrate digital commerce into the offline world. This process can be supported by most city councils. They should create more centrality for the city centers, especially in small and medium-sized towns. A city has to find its unique identity. It can build up attraction points for the city center as shopping location. This was the aim of the project "MG Retail.2020", using Mönchengladbach as a pilot city. The study produced a joint master plan for local retailers, the municipal policy and also the real estate industry. Core result was the concept of "Mönchengladbach on eBay" as a regional marketplace. This platform serves as a model for other cities. It has already received nationwide and international attention. The "Digital City" initiative launched by the German Retail Federation (HDE) and eBay is another outcome of the project.
Keywords: Einzelhandel; Stadtökonomie; Standort; Innenstadt; Online-Handel; Digitalisierung; Fallbeispiel